Denials and confessions: an analysis of the temporalization of neutralizations of corporate crime - Schoultz, Isabel (International journal of law, crime and justice, 2020)
In recent years two Swedish companies, Telia and Lundin Petroleum, have had to work hard to legitimate their actions as a result of allegations of criminal activity. In this paper, the corporate framings employed to deal with allegations of crime will be analysed on the basis of Stanley Cohen's (2009) theoretical work on processes of denial and neutralization techniques. More specifically, the paper focuses on the temporalization of neutralizations of corporate crime and aims to answer the following questions: How have the corporations' defence mechanisms changed over time? How might the types of crime of which they have been accused, and their corporate structures, affect the ways in which particular defence mechanisms are employed? The analysis demonstrates that although there are similarities, such as both companies framing their businesses as contributing to the development of democracy, human rights, prosperity and peace, the companies follow two different lines of development in their defences. While Telia moves from literal denial to confession, Lundin Petroleum stays with its literal denial in parallel with a strong condemnation of the condemners. These differences seem to be grounded both in the crimes of which the companies have been accused and their respective corporate structures.